Reading engagement matters!: a new scale to measure and support children's engagement with books
Reading engagement matters! Supporting behavioral, cognitive, affective, and social aspects of engagement will ensure all children have positive, rich, and diverse experiences with the books they read.
Keywords: Reading. -- Engagement. -- Children